2021
DOI: 10.1002/med.21777
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac efficacy and toxicity of aconitine: A new frontier for the ancient poison

Abstract: Aconitine (AC) is well‐known as the main toxic ingredient and active compound of Aconitum species, of which several aconites are essential herbal medicines of Traditional Chinese Medicine (TCM) and widely applied to treat diverse diseases for their excellent anti‐inflammatory, analgesic, and cardiotonic effects. However, the cardiotoxicity and neurotoxicity of AC attracted a lot of attention and made it a favorite botanic poison in history. Nowadays, the narrow therapeutic window of AC limits the clinical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…To fully explore the toxic mechanism of Fuzi, all the targets of Fuzi were subjected to KEGG analysis. Because the main toxicity of Fuzi includes cardiotoxicity and neurotoxicity, and disturbance of ion channels such as voltage-gated Na + channel is responsible for toxicity 26 , therefore calcium signaling, adrenergic signaling in cardiomyocytes, neuroactive ligand-receptor interaction, and dopaminergic synapse were considered as the toxic pathways of Fuzi. To help visualize the comprehensive toxic mechanism of Fuzi, a compound-target-pathway network was constructed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To fully explore the toxic mechanism of Fuzi, all the targets of Fuzi were subjected to KEGG analysis. Because the main toxicity of Fuzi includes cardiotoxicity and neurotoxicity, and disturbance of ion channels such as voltage-gated Na + channel is responsible for toxicity 26 , therefore calcium signaling, adrenergic signaling in cardiomyocytes, neuroactive ligand-receptor interaction, and dopaminergic synapse were considered as the toxic pathways of Fuzi. To help visualize the comprehensive toxic mechanism of Fuzi, a compound-target-pathway network was constructed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 ). Noteworthy is that disturbance of ion flow including Na + , Ca 2+ , and K + is the main reason for the toxicity of Fuzi 26 . Here we showed that Fuzi can act on multiple targets that directly modulate the flow of Na + , Ca 2+ , and K + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aconitum carmichaelii Debx is a TCM that is, used extensively in HF as the processed product of Aconitum carmichaelii Debeaux tubers ( Zhou W et al, 2021 ). Aconitum alkaloids, which include C19-diterpenoid alkaloids (mainly comprising aconitine, mesaconitine, and hypaconitine) and C20-diterpenoid alkaloids (predominantly benzoylmesaconitine, benzoylaconitine, and benzoylhypacoitine) and other alkaloids (mainly comprising higenamine and salsolinol) have versatile chemical structures ( Zhou et al, 2015 ).…”
Section: Mechanisms Of Traditional Chinese Medicine In Treating Heart...mentioning
confidence: 99%
“…Indole alkaloids, such as vinblastine and vincristine have indole skeletons and complex structures [ 11 ]. Terpenoids and steroidal alkaloids such as dendrobine, aconitine, and peiminine have a terpenoid or steroidal structure [ 12 , 13 ]. Alkaloids are well known for their high efficiency and low toxicity in antitumor activity.…”
Section: Introductionmentioning
confidence: 99%